Morphology and Topography of the Pancreatic Ducts during Posthatch Development in Kuttanad Duck (Anas platyrhynchos domesticus) - H. S. Patki, (Indian Journal of Veterinary Anatomy, 2022)
Posthatch development of the pancreatic ducts was studied in Kuttanad ducks using 78 female ducklingsfrom day of hatch to 24 weeks of age. The pancreas possessed three morphologically distinct extrapancreaticducts viz., chief dorsal, ventral and accessory dorsal extrapancreatic ducts, during the posthatch period. Ventralextrapancreatic duct drained ventral lobe whereas, dorsal lobe was jointly drained by chief dorsal extrapancreaticduct and accessory dorsal extrapancreatic duct. Chief dorsal extrapancreatic duct also drained splenic lobe. Allthe three extrapancreatic ducts opened separately in the ascending limb of duodenum in all the age groups.Theaccessory dorsal extrapancreatic duct was the first to open into the ascending limb of duodenum a few millimetresproximal to the apex of duodenal loop. It was followed by the opening sites of chief dorsal and ventralextrapancreatic ducts respectively, a few centimetres distally. Micrometrically, the diameter of ventralextrapancreatic duct was higher than chief dorsal extrapancreatic duct followed by accessory extrapancreaticduct. Intrapancreatic course of all the three ducts on radiographic study revealed that accessory dorsalextrapancreatic duct was direct continuation of caudal branch of chief dorsal pancreatic duct.